1991
DOI: 10.1007/bf00159976
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved oxygen concentration regulation using auto-tuning proportional-integral-derivative controller in fermentation process

Abstract: A novel control method involving an automatic tuning of digital proportional-integral--derivative controller parameters has been developed for better regulation of dissolved oxygen concentration by manipulating agitation speed in batch fermentation processes. Heuristic reasoning allows the proportional-integral--derivative controller to reach improved tuning decisions based upon the supervision of certain control performance indices in the same cognitive manner as in expert control.~-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The PID settings were obtained from process reaction curves by applying the Cohen-Coon tuning technique during different dynamic regimes, that were representing the lag, middleexponential, and late-exponential phase. Hwang et al (1991) used an algorithm which adapted the settings of the PID controller with a heuristic rule based on the supervision of certain performance indices. Lee et al (1994) have developed an autotuning PID DO controller with agitation rate as the manipulated variable.…”
Section: Do Control Overviewmentioning
confidence: 99%
“…The PID settings were obtained from process reaction curves by applying the Cohen-Coon tuning technique during different dynamic regimes, that were representing the lag, middleexponential, and late-exponential phase. Hwang et al (1991) used an algorithm which adapted the settings of the PID controller with a heuristic rule based on the supervision of certain performance indices. Lee et al (1994) have developed an autotuning PID DO controller with agitation rate as the manipulated variable.…”
Section: Do Control Overviewmentioning
confidence: 99%
“…The PID settings were obtained from process reaction curves by applying the Cohen-Coon tuning technique during different dynamic regimes, that were representing the lag, middle exponential, and late exponential phase. Hwang et al (1991) used an algorithm which adapted the settings of the PID controller with a heuristic rule based on the supervision of certain performance indices. Lee et al (1994) have developed an autotuning PID DO controller with the agitation rate as the manipulated variable.…”
Section: Introductionmentioning
confidence: 99%
“…Respiration rate is generally independent of DO above a certain critical level. Below that level a small change of the DO level may cause a significant physiological alteration in cell metabolism (Hwang et al, 1991). In secondary metabolite production, the optimal values for parameters such as pH, temperature, and DO may not be the same for growth and metabolite production (Lee et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that the respiration rate of aerobic microbe is generally independent of dissolved oxygen above a certain critical level. However, below that level, a small change in the dissolved oxygen may cause a significant physiological alteration in cell metabolism [9]. Supply of oxygen to the growing cell population is the rate-limiting step in many aerobic fermentation processes due to poor solubility of oxygen in the culture medium, which is determined by the oxygen transfer rate and is governed by the volumetric oxygen transfer coefficient (K L a), one of the most important parameters in scaling-up aerobic fermentation processes.…”
Section: Introductionmentioning
confidence: 99%